2018
DOI: 10.1097/md.0000000000013354
|View full text |Cite|
|
Sign up to set email alerts
|

Role of ethnicity and environment on lifestyle and cardiometabolic profile in the Native American Mapuche population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In particular, it has been demonstrated that circRNA are involved in cardiovascular disease initiation and progression, including atherosclerosis, cardiomyopathy, myocardial infarction, and cardiac fibrosis ( 17 ). In the present study, to determine whether the NPRA-related cardiometabolic profile (a term to describe a group of metabolic factors in cardiac associated with cardiovascular disease, metabolic syndrome and type II diabetes) ( 45 ) is associated with circRNAs, high-throughput screening of the DE-circRNAs was carried out using circRNA microarray analysis. To the best of our knowledge, the present study the first to use circRNA microarray analysis in NPRA −/− and NPRA +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been demonstrated that circRNA are involved in cardiovascular disease initiation and progression, including atherosclerosis, cardiomyopathy, myocardial infarction, and cardiac fibrosis ( 17 ). In the present study, to determine whether the NPRA-related cardiometabolic profile (a term to describe a group of metabolic factors in cardiac associated with cardiovascular disease, metabolic syndrome and type II diabetes) ( 45 ) is associated with circRNAs, high-throughput screening of the DE-circRNAs was carried out using circRNA microarray analysis. To the best of our knowledge, the present study the first to use circRNA microarray analysis in NPRA −/− and NPRA +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the article, “Role of ethnicity and environment on lifestyle and cardiometabolic profile in the Native American Mapuche population: Protocol for a systematic review and meta-analysis”, [1] which appeared in Volume 97, Issue 48 of Medicine , the Extraction Form was not included with the appendices and can be found at.…”
mentioning
confidence: 99%